2022
DOI: 10.1007/s10072-022-06158-w
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the preoperative inflammatory index on the survival of glioblastoma patients

Abstract: Objectives The growth and development of tumors are closely related to the initiation and amplification of the inflammatory response. Various inflammatory biomarkers had attained growing attention for nearly two decades and were discovered strongly associated with cancer patients’ prognosis, indicating that systemic inflammatory response is possibly essential to cancer progression. However, little was known about the sensitive biomarkers associated with the detection, persistence, treatment, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…In addition, five studies were discarded based on the reasons such as the nonavailability of survival information ( n = 3), no analysis of the SII ( n = 1), and the enrollment of overlapped patients ( n = 1). As a result of this meta-analysis, we enrolled eight articles including 1,426 cases ( 15 22 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, five studies were discarded based on the reasons such as the nonavailability of survival information ( n = 3), no analysis of the SII ( n = 1), and the enrollment of overlapped patients ( n = 1). As a result of this meta-analysis, we enrolled eight articles including 1,426 cases ( 15 22 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past, SII has been demonstrated to have a significant prognostic effect in a wide variety of cancers in many studies, including gastric cancer (GC) ( 10 ), cervical cancer (CC) ( 11 ), renal cell carcinoma (RCC) ( 12 ), diffuse large B-cell lymphoma (DLBCL) ( 13 ), and melanoma ( 14 ). SII has also been investigated in numerous studies to be the prognosis prediction biomarker for glioma cases; however, results have been inconsistent ( 15 22 ). For example, some researchers reported elevated SII as the important biomarker to predict the prognosis of glioma cases ( 17 , 19 , 20 ), whereas some other scholars found no evident relation of SII with glioma prognosis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duplicate studies were excluded, and conference abstracts or studies lacking sufficient data were excluded after full-text evaluation. Five studies that enrolled 788 patients were included in the final metaanalysis [20][21][22][23]26]. The selection process of the meta-analysis is shown in Supplementary Figure S1.…”
Section: A Meta-analysis Evaluating the Prognosis Of Sii In Patients ...mentioning
confidence: 99%
“…The systemic immune-inflammation index (SII) [17], a novel inflammatory biomarker calculated by platelet count*neutrophil count/lymphocyte count, has been determined to be related to worse outcomes in many cancer patients, including breast cancer [18], hepatocellular carcinoma [19] and glioma [20]. Two recent studies reported that a higher SII was associated with a worse outcome in the GBM cohort [21,22]. However, the prognostic value of the SII is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…They did not assess their prognostic capacity in comparison to the current tumour staging systems. 20,42,43 In our study, by incorporating inflammatory biomarkers and other clinicopathological factors, we built a simple but reproducible model that had higher prognostic power than common staging systems. It is undeniable that our research has some limitations.…”
mentioning
confidence: 99%